Development of Run Ping-Pong Ball Game Media to Train Students’ Memory Skills - Novia Ramadani; Ahmad Syarqawi (Yayasan Sembilan Pemuda Indonesia, 2027)
Elementary school students may experience difficulty maintaining concentration, retaining information, and recalling recently learned material. This study aimed to develop Run Ping-Pong Ball game media and evaluate its validity and practicality as a tool for training memory skills in classical guidance services. The study employed a Research and Development approach using the 4D model, limited to the Define, Design, and Develop stages. Participants were 26 fourth-grade students at SD Swasta Al-Mukmin. Data were collected through interviews, observations, expert-validation questionnaires, a guidance counselor response questionnaire, and a student response questionnaire. The needs analysis indicated problems related to attention, short-term recall, concentration, and information retention, as well as a preference for active and experience-based media. The media expert awarded a validity score of 84%, and the material expert awarded 93.33%, placing the product in the highly valid category. The guidance counselor’s practicality score was 94%, while the students’ response score was 82.46%, indicating high practicality. The developed game combines physical movement, sequential instructions, and information recall in an enjoyable activity. These findings demonstrate that the product is feasible for limited use in classical guidance services. However, effectiveness in improving memory was not measured and should be examined through experimental research.